Motion events in English textbooks: a cross-linguistic analysis of Path - Banaruee, Hassan; Khatin-Zadeh, Omid; Farsani, Danyal (Frontiers in Education, 2023)
Understanding how motion events are encoded and retrieved across languages has significant implications for language teaching, learning, and cognitive linguistics. However, there is hardly any research in this area comparing the motion-related lexical patterning of English textbooks. To this aim, this research was conducted to fill this gap. Primarily, we investigated the motion-related patterns in three textbooks taught in countries with different language classes according to motion typology (Slobin, 2004;Talmy, 1985). They were Verb-framed (Turkish), Satellite-framed (Australian English), and Equipollently-framed (Persian). Three novels in each source language were analyzed to discover the effect of these languages on the development of teaching materials.This provided the research with deep insights into Talmy's categorization. The results from the corpus displayed a weak modification of English in EFL textbooks in Iran and Turkey that might have stemmed from their source language cognitive styles. The results also indicated that the degree of emphasis on Path were close in these three languages, which demands a revisit of Talmy's classification.